ANALISIS PENGARUH STRUKTUR KEPEMILIKAN PERUSAHAAN TERHADAP BIAYA AUDIT - Benna Andriyani; Herry Laksito (Diponegoro Journal of Accounting, 2017)
The purpose of this study is to observe the relationship between the ownership structure of the company, namely managerial ownership, foreign ownership, and government ownership as an independent variables to the audit fee agreed by the external auditor. Furthermore, the audit fee illustrate how the client's internal control level was going and the agency conflict that may occur.The type of data used in this study is secondary data and involves 173 public companies in Indonesia. The sampling method in this research uses purposive sampling technique for the company that has been listed in Indonesia Stock Exchange which publishes annual report in 2015 and discloses voluntary information about audit fee and the composition of share ownership of company. The analysis technique used is multiple linear regression analysis with OLS model.This study uses agency theory to formulate three hypotheses that lead to the results of the analysis. The results showed a significant positive effect between the foreign and government ownership structure on the audit fee. While managerial ownership is negatively but not significant.